NCs in Moghamo prenasalized onsets or heterosyllabic clusters - Roderic F. Casali (LibraryPress@UF, 1995)
This paper is concerned with the analysis of nasal-plus-oral-stop sequences in Moghamo, a Grassfields Bantu language of Cameroon. Although Stallcup [1978] tentatively analyzed these sequences as heterosyllabic clusters, the evidence suggests that they are actually prenasalized syllable onsets. First, the distribution of NCs closely parallels that of unambiguous onsets: they occur both initially and medially in words of several grammatical categories. Instances of unambiguous heterosyllabic clusters, by contrast, are rare. Second, while the nasal portion of noun-initial NCs was historically a prefix, it appears to be part of the root synchronically. Third, the nasal portion of an Niger-Congo does not appear to be phonologically tone-bearing. Finally, the contention that NCs are on-sets is supported by native speaker intuitions.